Analisis Modal Sosial (Trust, Network, and Norms) Rumah Tangga Petani Pada Masa Pandemi Covid-19 di Desa Pasirtalaga, Kecamatan Telagasari, Kabupaten Karawang - Fatimah Azzahra; Kuswarini Sulandjari (Institut Pertanian Bogor, 2022)
The worldwide Covid-19 pandemic has had a tremendous influence on society, notably on farmer households in Desa Pasirtalaga, Kecamatan Telagasari, Kabupaten Karawang. The Covid-19 virus, as well as government regulations such as PPKM, can be a stressor that puts farming households in crisis situation. Farmer households' social capital is one of their buffer capacities that can be used as a basis in times of distress. The goal of this study is to look at farmer households' social capital in terms of the three components of social capital: norms, networks, and trust. Purposive sampling was employed to determine the approach used in this study, which is a quantitative method backed by qualitative data. Respondents were 40 farmer households which were determined by purposive sampling method. The results of this study indicate that the social capital of farmer households in Desa Pasirtalaga is of high value, especially in the level of compliance with norms, and the level of trust in the social environment. So, it can be concluded that social capital is very important for farmer households in Pasirtalaga Village during the covid-19 pandemic.